الوضعيات القانونية الاساسية للموظف العام وحركة نقله اثناء الخدمة - غربي, ايواب; رابحي, راضوان (University of Eloued جامعة الوادي, 2020)
يمر الموظف العام أثناء مسيرته الوظيفية ببعض الوضعيات والمحددة بموجب نص المادة 127 من الأمر 06/03 المتعلق بالوظيفة العمومية، تتمثل هذه الوضعيات في وضعية القيام بالخدمة أو ما تسمى بوضعية الخدمة الفعلية التي يكون فيها الموظف ممارسا للمهام المنوطة إليه والتي تتناسب مع رتبته ومنصب شغله في الإدارة أو المؤسسة التي ينتمي إليها، كما توجد وضعية الانتداب وهي الوضعية التي يكون فيها الموظف خارج سلكه الأصلية إلا أنه يستفيد من حقه في الترقية في الدرجة ويحتسب له الأقدمية سواء في التقاعد أو الترقية، بالإضافة إلى وضعية خارج الإطار التي يمكن أن يوضع فيها الموظف بطلب منه بعد أن يستنفد حقه في الانتداب. يمكن للموظف العام أن يطلب نقله لأسباب مختلفة كما أنه يمكن أن يتم نقله إجباريا من طرف الإدارة أو المؤسسة التي يمارس بها مهامه لضرورة المصلحة أو لعقوبة تأديبية. The public employee passes with some position during his career pathn, which are determined under the text article 127 of the order 06/03 related to the public employment. This posi tious are represented in the tionof performerg the service or what is called the actual service by which the employee is practicing the tasks that are assigned to him, and it is commensur ate with his rank, and position iu the administration or the instituation in which he belongs. There also the mandoti status in which the employee is being outside his original line or administration. Aowever, he benifits from his right to up grade in the rank and seniority is calculated for him, whether in retirement or promotion, in addition to the si tuation of out si de the fram work in which the imployee con be placed at his request after he exhusts his right to mandate. The employee con request his transfer for vorious reosons, also he can be obligatory trausfered by the administion or the instituation in which he exercises his work due to the neccessity of the interest, or for a disciplinory punishment.
مذكرة ماستر
Keywords: الموظف .الخدمة; Employee.Service